Functional Lateralization of Speech Processing in Adults and Children Who Stutter - Sato, Yutaka; Mori, Koichi; Koizumi, Toshizo; Minagawa-Kawai, Yasuyo; Tanaka, Akihiro; Ozawa, Emi; Wakaba, Yoko; Mazuka, Reiko (Frontiers in Psychology, 2011)
Developmental stuttering is a speech disorder in fluency characterized by repetitions, prolongations and silent blocks, especially in the initial parts of utterances. Although their symptoms are motor related, people who stutter show abnormal patterns of cerebral hemispheric dominance in both anterior and posterior language areas. It is unknown whether the abnormal functional lateralization in the posterior language area starts during childhood or emerges as a consequence of many years of stuttering. In order to address this issue, we measured the lateralization of hemodynamic responses in the auditory cortex during auditory speech processing in adults and children who stutter, including preschoolers, with near-infrared spectroscopy (NIRS). We used the analysis-resynthesis technique to prepare two types of stimuli: (i) a phonemic contrast embedded in Japanese spoken words (/itta/ vs. /itte/) and (ii) a prosodic contrast (/itta/ vs. /itta?/). In the baseline blocks, only /itta/ tokens were presented. In phonemic contrast blocks, /itta/ and /itte/ tokens were presented pseudo-randomly, and /itta/ and /itta?/ tokens in prosodic contrast blocks. In adults and children who do not stutter, there was a clear left-hemispheric advantage for the phonemic contrast compared to the prosodic contrast. Adults and children who stutter, however, showed no significant difference between the two stimulus conditions. A subject-by-subject analysis revealed that not a single subject who stutters showed a left advantage in the phonemic contrast over the prosodic contrast condition. These results indicate that the functional lateralization for auditory speech processing is in disarray among those who stutter, even at preschool age. These results shed light on the neural pathophysiology of developmental stuttering.